RESEARCH ARTICLE ON IMPROVING THE APPRECIATION AND RISE STATUS OF PUBLIC SCHOOL TEACHERS IN UZBEK SOCIETY (Web of Teachers: Inderscience Research, 2025)
Teaching has always been an inseparable part of any society; consequently, teachers have played an essential role for the development of the social life of the community. Depending on different circumstances the social status of teachers varied from time to time, from country to country. This case study focused on the analysis of status of teacher career pathways in Uzbekistan, identifies challenges in improving the status of public-school teachers and provides recommendations on effective reforms in Uzbekistan, by exchanging the experience of other countries performing well in education rankings.